THE ASSESSMENT OF OVERHEATING COMPOSITE PADS ON THE MOUNTAIN AREAS - Kvantaliani, H. H.; Korzhenevych, Y. P.; Todua, T. H.; Toropov, B. Y. (Science and Transport Progress, 2008)
The methods of estimation of overheat of composition brake shoes on mountain pass sections are considered.